Googling the Guggul (Commiphora and Boswellia) for Prevention of Chronic Diseases - Kunnumakkara, Ajaikumar B.; Banik, Kishore; Bordoloi, Devivasha; Harsha, Choudhary; Sailo, Bethsebie L.; Padmavathi, Ganesan; Roy, Nand K.; Gupta, Subash C.; Aggarwal, Bharat B. (Frontiers in Pharmacology, 2018)
Extensive research during last two decades has revealed that most drugs discovered today, although costs billions of dollars for discovery, and yet they are highly ineffective in their clinical response. For instance, the European Medicines Agency has approved 68 anti-cancer drugs, and out of which 39 has reached the market level with no indication of increased survival nor betterment of quality of life. Even when drugs improved survival rate compared to available treatment strategies, most of these were found to be clinically insignificant. This is a fundamental problem with modern drug discovery which is based on thinking that most chronic diseases are caused by alteration of a single gene and thus most therapies are single gene-targeted therapies. However, extensive research has revealed that most chronic diseases are caused by multiple gene products. Although most drugs designed by man are targeted therapies, however, those designed by “mother nature” and have been used for thousands of years, are “multi-targeted” therapies. In this review, we examine two drugs that have been around for thousands of years, are called “guggul” from Commiphora and Boswellia. Although we are all familiar with the search engine “google”, this is another type of “guggul” that has been used for centuries and being explored for its various biological activities. The current review summarizes the traditional uses, chemistry, in vitro and in vivo biological activities, molecular targets, and clinical trials performed with these agents.